MicroRNA-16 and MicroRNA-424 regulate cell-autonomous angiogenic functions in endothelial cells via targeting VEGFR2 and FGFR1 - Chamorro-Jorganes, Aránzazu (2011)
OBJECTIVE: microRNAs play key roles in modulating a variety of cellular processes by post-transcriptional regulation of their target genes. VEGF, VEGFR-2 and FGFR-1 were identified by bioinformatic approaches and subsequently validated as targets of miR-16 and miR-424 in endothelial cells (ECs). RESULTS/METHODS: Mimetics of these microRNAs reduced VEGF, VEGFR-2 and FGFR-1 expression, whereas specific antagonists enhanced their expression. Expression of mature miR-16 and miR-424 was up-regulated upon VEGF or bFGF treatment. This up-regulation was accompanied by a parallel increase in pri-miR-16-1 and pri-miR-16-2 but not in pri-miR-424 levels, indicating a VEGF/bFGF-dependent transcriptional and post-transcriptional regulation of miR-16 and miR-424, respectively. Reduced expression of VEGFR2 and FGFR1 by miR-16 or miR-424 overexpression regulated VEGF and bFGF signaling through these receptors, thereby affecting the activity of downstream components of the pathways. Functionally, miR-16 or miR-424 overexpression reduced proliferation, migration and cord formation of ECs in vitro and, lentiviral overexpression of miR-16 reduced the ability of ECs to form blood vessels in vivo. CONCLUSION: We conclude that these miRNAs finely tune the expression of selected endothelial angiogenic mediators in response to these growth factors. Altogether, these findings suggest that miR-16 and miR-424 play important roles in regulating cell-intrinsic angiogenic activity of ECs.